Rational Design of Inflammation-Responsive Inflatable Nanogels for Ultrasound Molecular Imaging - Heo, Jeongyun; Lim, Chang-Keun; Min, Hyun Su; Lee, Kyung Eun; Jeong, Keunsoo; Seo, Young Hun; Lee, Yong-Deok; Yhee, Ji Young; Kim, Kwangmeyung; Kwon, Ick Chan; Park, Soo Young; Kim, Sehoon (AMER CHEMICAL SOC, 2019)
Microbubbles are clinically used as an imaging agent for contrast-enhanced ultrasound image. Beyond the preformed microbubbles, nanoscale gas-generating chemical systems that are capable of stimulus-responsive inflation to microbubbles have recently been employed as a new echogenic strategy for ultrasound molecular imaging. Here, we report a peroxamide-based ultrasound contrast agent as a H2O2-responsive gas (CO2)-generating system for diagnostic ultrasound imaging of inflammatory diseases. A hydrolytic degradation-resistant peroxamide nanogel was constructed by nanoscopic cross-linking of polymeric aliphatic amines (branched polyethyleneimine) with oxalyl chloride, which intrinsically offers highly concentrated peroxamides as a reactive cross-linking point for H2O2-responsive CO2-generation by the peroxalate chemiluminescence reaction that is intrinsically catalyzed by the polyamine-derived intraparticle basic environment. It was experimentally revealed that the interior of the peroxamide-concentrated nanogel colloid serves as an optimal nanoscale catalytic reactor for the H2O2-responsive gas generation as well as a gas reservoir capable of nano-to-micro inflation. We demonstrate that the peroxamide-concentrated nanogels are indeed capable of enhancing the ultrasound contrast in response to H2O2, which allows us to perform diagnostic ultrasound imaging of H2O2-overproducing inflammatory diseases in mouse models. Along with the biocompatibility of the peroxamide nanogels revealed by the animal toxicity study, our design strategy for the inflatable nanoparticles would contribute to the advancement of activatable contrast agents for ultrasound molecular imaging.
Keywords: HYDROGEN-PEROXIDE; CONTRAST AGENTS; POLYMERIC NANOPARTICLES; LIVER-INJURY; CHEMILUMINESCENCE; DELIVERY; MICROSPHERES; OXYGEN; ALPHA; TUMOR